A Study of Social Work Students' Knowledge and Perceptions of Stages of Latino Immigration. (2nd January 2018) - Held, Mary Lehman; Cuellar, Matthew J.; Cook Heffron, Laurie
ABSTRACT: Latino immigrants encounter distinct hardships at each stage of the immigration process, including stressors that occur in the home countries, during travel, and on settlement, which correspond with poorer mental health status. Yet, much of social work education and service delivery centers only on postsettlement needs. This exploratory study provides descriptive data on 194 social work students' experiences with and perceptions of Latino immigration and analyzes how students' perceived preparedness to work with Latino immigrants corresponds with their knowledge of hardships during each immigration stage. Findings suggest that students felt moderately prepared to work with immigrants and that perceived preparedness was positively associated with familiarity of immigration stage stressors. Implications for social work education, practice, and research are presented.